Heterogeneity of Helicobacter pylori bab genotypes and their association with clinical outcomes in Korean gastroduodenal patients - Wongwarut Boonyanugomol (2022)
In this study, we aimed to investigate the prevalence of bab genes (babA, babB, babC) at their three loci (loci A, B, and C) in Helicobacter pylori strains from varied clinical manifestations of Korean gastroduodenal patients. The overall prevalence of H. pylori Korean strains positive for babA and babB was 91.1% and 92.2%, respectively, but all strains were negative for bab C. H. pylori strains with two loci occupied (loci A and B) were the most prevalent in Korean patients (85.6%), compared to one locus occupied (14.4%) (locus A or B). Twelve bab genotypes were detected, additionally, the distribution of three bab genotypes was significantly associated with different clinical outcomes among Korean patients. The genotypes babA/babB/- and babA/babA were significantly associated with peptic ulcer disease (PUD) (63.3%) and gastritis (GT) (33.3%) patients, respectively. In addition, we found that the babA genotype was significantly associated with gastric cancer (GC) (36.7%) as compared to GT (6.7%) or PUD (6.7%) (p<0.05) patients. This study provided evidence that the bab genotypes in H. pylori Korean strains were highly variable. Interestingly, three patterns of bab genotypes were significantly different among patients with different clinical outcomes in the population at high-risk for GC.